Synergy of Ion Doping and Spiral Array Architecture on Ti2Nb10O29: A New Way to Achieve High‐Power Electrodes. (29th April 2020) - Deng, Shengjue; Zhu, He; Liu, Bo; Yang, Liang; Wang, Xiuli; Shen, Shenghui; Zhang, Yan; Wang, Jiaao; Ai, Changzhi; Ren, Yang; Liu, Qi; Lin, Shiwei; et al.
Abstract: Ameliorating electronic/ionic transport and structural stability of electrode materials is important to the development of power‐intensive lithium ion batteries. Despite its great potential as a high‐power anode, titanium niobium oxide (Ti2 Nb10 O29, TNO) still underperforms due to its unsatisfactory electronic/ionic conductivity. In this work, a powerful synergistic strategy by combining ion doping and spiral array architecture to boost high‐rate performance of TNO is reported. Cr 3+ doped TNO nanoparticles (Cr‐TNO) of 5–10 nm intimately grow on a conductive vertical graphene@TiC‐C (VGTC) skeleton, forming novel Cr‐TNO@VGTC spiral arrays. The unique spiral growth of TNO is achieved due to the confinement effect of VGTC skeleton. Meanwhile, a more open TNO crystal structure with faster ion transfer paths and enhanced structural stability is realized by Cr 3+ doping, demonstrated via density functional theory calculation and in situ synchrotron X‐ray diffraction technique. Benefiting from the superior conductive network, enhanced intrinsic electronic/ionic conductivity of Cr‐TNO and reinforced structural stability, the Cr‐TNO@VTC arrays show prominent high‐power performance with a large capacity of 220 mAh g −1 at 40 C (power density of ≈11 kW kg −1 ) and superior durability (91% retention after 500 cycles). This work provides a new path for the construction of widespread high‐power electrodes for fast energy storage. Abstract : In this work, a new synergistic strategy by combing ion doping and spiral array architecture on titanium niobium oxide (TNO) to boost high‐rate performance is reported. Typically, Cr 3+ ‐doped TNO nanoparticles (Cr‐TNO) 5–10 nm in size intimately grow on the conductive vertical graphene@TiC‐C skeleton (VGTC), forming Cr‐TNO@VGTC spiral arrays. The designed Cr‐TNO@VTC arrays are demonstrated with prominent high‐power performance.